EXPLORATION OF FACTORS OF RURAL DEVELOPMENT IN CENTRAL SERBIA - Čobanović, Katarina; Nikolic-Djoric, Emilija; Mutavdžić, Beba (Economics of Agriculture, 2006)
The analysis of influence of social–economic factors is important in analysis of demographic development of population in Central Serbia. The development of each society is significantly implied with interaction of demographic and socialeconomic factors. In the paper the relevant indicators of demographic development of population in Central Serbia are explored. The combined data from population census and yearly published data related to communes and districts of Central Serbia were used. The estimated empirical regression models based on chosen variables ought to illustrate the reached level of demographic development in Central Serbia. The relations of following variables are analyzed: total number of inhabitants, number of active persons, number of agriculturists per 100 populations, rate of employment, national income, rates of natural increase, birth and mortality etc.